2014
DOI: 10.1371/journal.pone.0113741
|View full text |Cite
|
Sign up to set email alerts
|

Burden of Diabetes Mellitus Estimated with a Longitudinal Population-Based Study Using Administrative Databases

Abstract: ObjectiveTo assess the epidemiologic and economic burden of diabetes mellitus (DM) from a longitudinal population-based study.Research Design and MethodsLombardy Region includes 9.9 million individuals. Its DM population was identified through a data warehouse (DENALI), which matches with a probabilistic linkage demographic, clinical and economic data of different Healthcare Administrative databases. All individuals, who, during the year 2000 had an hospital discharge with a IDC-9 CM code 250.XX, and/or two co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
19
0
2

Year Published

2016
2016
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 17 publications
(17 reference statements)
3
19
0
2
Order By: Relevance
“…In this cost-of-illness study we analyzed the annual direct medical costs of a population of patients with T2DM comprising over 70% elderly, a large majority (72.9%) with a duration of illness > 5 years, and 65.6% with two or more chronic conditions. The mean annual medical cost per capita was €3086, consistent with the results of other studies conducted in Italy or in Europe [7,8,11,23,32]. However, the median annual medical cost (€1012) is a more accurate summary measure because the distribution of costs is skewed, with a few patients accounting for a large proportion of costs, in line with other studies [10,12].…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…In this cost-of-illness study we analyzed the annual direct medical costs of a population of patients with T2DM comprising over 70% elderly, a large majority (72.9%) with a duration of illness > 5 years, and 65.6% with two or more chronic conditions. The mean annual medical cost per capita was €3086, consistent with the results of other studies conducted in Italy or in Europe [7,8,11,23,32]. However, the median annual medical cost (€1012) is a more accurate summary measure because the distribution of costs is skewed, with a few patients accounting for a large proportion of costs, in line with other studies [10,12].…”
Section: Discussionsupporting
confidence: 89%
“…However, the median annual medical cost (€1012) is a more accurate summary measure because the distribution of costs is skewed, with a few patients accounting for a large proportion of costs, in line with other studies [10,12]. We confirmed that hospitalization accounts for the large majority of costs (53.1%) followed by drugs (29.5%) and outpatient services (17.4%) [7,8,11,23].…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…The costs of the end-stage organ damage health states were obtained from the Italian literature and international studies when no local cost was available [56,57,58,59,60]. Cost data are presented in 2015 in EUR.…”
Section: Methodsmentioning
confidence: 99%
“…A SMART is a special case of the factorial experiment involving randomization at several stages, where each stage corresponds to one of the decisions that must be made about adapting the intervention, and some or all of the randomization may be contingent on response to treatment. 34, 40, 44 …”
Section: Research Questionsmentioning
confidence: 99%